Foraging activity of the social wasp Polybia emaciata (Hymenoptera: Vespidae: Polistinae) - López G., Yeison; Hernández D., John; Caraballo, Pedro (Revista Colombiana de Entomología, 2013)
To characterize foraging activity of the social wasp Polybia emaciata nests were installed in three commercial monocultures (4 nests/culture) in the Colombian Caribbean Region. Observations were made for 36 days between 06:00 and 18:30 hours, with an average of 20 hours of observation per nest and 80 hours per crop. Foragers returned with liquid in 53.2% of the cases, with solid prey in 27.2%, and with building materials in 9.1%; the remaining 11.4% did not carry identifiable loads. The solid diet included prey from the orders Diptera (32.2%), Coleoptera (31%), Hemiptera (13.4%), Lepidoptera (8.8%), Hymenoptera (5.4), Neuroptera (0.8%), Orthoptera (1.1%), Araneae (1.9%), and Isopoda (0.4%); the remaining 5% was no identifiable. Adult insects from families Tephritidae, Chrysomelidae and Lonchaeidae were the most common prey. High temperatures and low relative humidity positively influenced foraging activity. A projection of the data suggests that a nest of P. emaciata may receive 78 prey per day. These results allows quantitative estimates for the use of P. emaciata as an alternative biological control tool for agroecosystems in this region.